Epigenetic memory: the Lamarckian brain. (9th April 2014) - Fischer, Andre
Abstract Recent data support the view that epigenetic processes play a role in memory consolidation and help to transmit acquired memories even across generations in a Lamarckian manner. Drugs that target the epigenetic machinery were found to enhance memory function in rodents and ameliorate disease phenotypes in models for brain diseases such as Alzheimer's disease, Chorea Huntington, Depression or Schizophrenia. In this review, I will give an overview on the current knowledge of epigenetic processes in memory function and brain disease with a focus on Morbus Alzheimer as the most common neurodegenerative disease. I will address the question whether an epigenetic therapy could indeed be a suitable therapeutic avenue to treat brain diseases and discuss the necessary steps that should help to take neuroepigenetic research to the next level.